Diffuse interstellar bands and the structure of the ISM - Cordiner, Martin (2005)
Results are presented of three different studies into the nature of the diffuse interstellar bands, their carriers and the environments in which they are located. 1. Optical observations of small-scale structure in the distribution of large molecules and/or dust grains in the ISM are examined in the first dedicated study of its type. Evidence is presented for variation in the strengths of fifteen out of sixteen measured narrow diffuse interstellar bands, over spatial scales from ~ < 370 AU to ~ < 20000 AU, observed towards the component members of nearby (< 1.5 kpc distant) early-type binary and multiple star systems. Variations in diffuse interstellar band (DIB) equivalent widths of about five to ten percent are found between the sightlines towards rho Oph A and B (separated by approximately 370 AU in the plane of the sky). The lambda 5780, lambda 5797, lambda 5850, lambda 6376, lambda 6379, lambda 6439, lambda 6614 and lambda 6660 DIBs are found to be significantly stronger towards rho Oph B by an amount comparable to the differences in the column densities of interstellar K I and Ca II in these sightlines. The upper limit on the variability of the lambda 6284 DIB is approximately 1.5%. Different DIBs are subject to different degrees of variation, and in some cases different signs of variation, for example the lambda 5850 DIB is stronger towards rho Oph C than rho Oph A, whereas lambda 6614 is stronger towards A than C, proving the existence of chemical differences between the DIB carriers. The lambda 6614 DIB is found to show a variation in its pattern of sub-structure between rho Oph A and C, which, interpreted within the `Webster hypothesis' (Webster 1996), is consistent with a- 4% enhancement in the interstellar [12C]/[13C] ratio towards rho Oph A relative to C. In other star systems observed: The lambda 5780, lambda 6196 and lambda 6614 diffuse interstellar bands are found to be stronger towards ß2 Sco than ß1 Sco (sightlines separated by ~ 2200 AU). The lambda 6614 DIB is found to be stronger towards HD 150136 than HD 150135 (~ 12,500 AU separation) but no significant variation is found in the strengths of any other DIBs in the spectra of this binary system. The lambda 5780, lambda 6196 and lambda 6614 DIBs are detected in the lightly-reddened sightlines towards the two members of the mu Cru system, and are found to be approximately 50 to 200% stronger towards mu2 Cru than mu1 Cru. Weak interstellar K I absorption is detected and is found to be 122 ± 80% stronger (at 1delta- confidence) towards mu2 Cru than mu1 Cru. The lambda 5780, lambda 6196, lambda 6203 and lambda 6614 diffuse interstellar bands are detected in the well-known `time-variable' sightline towards kappa Vel. Spectra are presented that show the interstellar K I column density in this sightline to be N(K I) = 3.43 ±0.13 x 1010 cm-2 in June 2004, corresponding to approximately a 35% increase in N(K I) since the time of the last measurement in March 2002 by Crawford (2002). During this period, the sightline moved ~<5 AU. DIB strengths towards kappa Vel are compared between observations made in January 1995 and June 2004, during which time the sightline moved ~< 25 AU across the interstellar medium (ISM) and the neutral potassium column density approximately doubled. No significant variation in the strength of lambda 5780 is found, with an upper limit on the change in equivalent width of ±41 %. The variation of diffuse interstellar band strengths over small spatial scales is interpreted as due to variations in the abundances of the carriers. Possible causes of small-scale DIB variability are discussed, including the degree of ionisation and excitation of the carriers. 2. The hypothesis that the cyanomethyl anion CH2CN- is responsible for the relatively narrow diffuse interstellar band at 8037.8 ± 0.15 angstrem is examined. The absorption spectrum arising from the 1B1 <-- 1A' origin band transition from the ground electronic state to the first dipole-bound state of the anion is calculated. Assuming that the distribution of ground state rotational level populations is in thermal equilibrium with the 2.74 K cosmic microwave background radiation, the transition results in a rotational contour with a peak wavelength of 8037.78 angstrem. CH2CN- is found to be a plausible candidate for the carrier of the lambda 8037 diffuse interstellar band provided a mechanism exists by which the rotational contour is broadened by an approximately Gaussian dispersion function with a width characterised by a Doppler b parameter between 16 and 33 km s-1 depending on the specific sightline in which the DIB is observed. Doppler broadening is found to be sufficient to cause such a dispersion in heavily-reddened sightlines, as demonstrated by the velocity structure of the interstellar gas in the sightline towards HD 183143, which is examined for K I, Na I, Ca I, Ca II, Ti II, CH, CH+ and CN. Convolution of the calculated CH2CN- transitions with the optical depth profile of either Ca n or Ti n successfully reproduces the profile of the narrow lambda 8037 DIB observed towards HD 183143. The 2.74 K thermal distribution of ground-state rotational level populations may be modified by the nuclear spin statistics of the molecule. This situation is modelled and results in the appearance of additional strong spectral features at around 8024.8 angstrem and 8049.6 angstrem that are not seen in the observed interstellar spectra. If (a) no chemical mechanisms exist for the conversion of `ortho' CH2CN- (hydrogen nuclear spins parallel) to `para' CH2CN' (hydrogen nuclear spins antiparallel) or (b) the CH2CN- formation mechanisms do not result in a distribution of Kä levels approaching a 2.74 K Boltzmann distribution, then it is found that CH2CN' cannot be the carrier of the A8037 diffuse interstellar band. 3. The strengths of diffuse interstellar bands and atomic lines in the ISM of the Large Magellanic Cloud (LMC) are analysed and compared with Galactic data. Using optical spectra obtained along six reddened sightlines towards early-type stars in the LMC, at a resolution of -3 km s'1 and a signal-to-noise of - 200, the velocity structure and column densities of interstellar K I, Na I, Ca II and Ti II are derived. Evidence is presented that the spectrum of diffuse interstellar bands in the LMC is similar (in strength and structure) to that found in the Galaxy, with the measurement of the equivalent widths of eleven DIBs at the Doppler-shifted wavelengths expected for the radial velocity of the LMC, including lambda 4430, lambda 5705, lambda 5780, lambda 5797, lambda 5850, lambda 6196 lambda 6203, lambda 6284, lambda 6376, lambda 6379 and lambda 6614. The observation of lambda 5705, lambda 5850, lambda 6196 and lambda 6203 constitutes the first reported detection of these DIBs in the LMC, and for lambda 5850, in any location outside of the Galaxy. All of the expected DIBs were observed towards the 30 Dor targets Sk -69°223 and Sk -69°243, and with strengths approximately equal to, or only slightly weaker than, those in Galactic `v-type' (strongly UV irradiated) sightlines with similar reddenings and neutral potassium column densities. This result shows that there are interstellar clouds in the vicinity of 30 Dor that provide favourable environments for the existence of DIB carriers. The velocities of the carriers of the lambda 5780, lambda 5797, lambda 5850, lambda 6196, lambda 6379 and lambda 6614 diffuse interstellar bands in the LMC are found to be coincident with the velocities of the peaks of the atomic column density distributions at radial velocities of between 240 and 300 km s-1 relative to the local standard of rest. The least-squares fitted velocity of the A6614 DIB is found to be shifted by - +5 km s-1 relative to the other DIBs in three out of four sightlines. This may be interpreted as evidence that the profile of sub-structure of the lambda 6614 DIB is skewed towards the red in these three sightlines (Sk -68°135, Sk -69°223 and Sk -69°243) to a greater degree than that found in the Galactic ISM. Compared to Galactic trends, the LMC DIBs are found to be weak with respect to the reddening and neutral potassium column density towards Sk -67°2 and Sk -68°135. This may be attributable to a combination of the high UV flux and reduced shielding of interstellar clouds due to the low metallicity of the interstellar gas of the LMC, and results in the destruction of DIB carriers by photodissociation and/or photoionisation. Relative to N(H I) the lambda 6284 DIB observed in four LMC sightlines is shown to be approximately 1/5 to 1/2 of its average strength in the Milky Way. This supports the idea that the metallicity and/or dust-to-gas ratio of the ISM is closely linked with the chemistry that governs the abundance of DIB carriers relative to N(H I). Variations in the N(Ca II)/N(Ti II) ratio are found over at least an order of magnitude in the LMC ISM, and are taken as evidence for significant variation in the Ca n/Ca m ionisation balance. Derived logarithmic titanium depletions are found to be relatively low in the six LMC sightlines studied, with values between approximately -0.8 and -1.9, which are similar to the levels of depletion generally seen in the warm, shocked interstellar medium of the Galaxy.